The study of thick corrosion layers on archaeological metals using controlled laser ablation in conjuction with an external beam microprobe - Abraham, M; Grime, G; Marsh, M; Northover, J (2001)
The variation with depth of the composition of corrosion layers on buried metal objects can provide the archaeologist with valuable information relating to the burial conditions of the object. In some cases these layers can be varied in thickness (up to 1 mm) and so normally destructive methods such as sampling are used to characterise the metal and corrosion layers when possible. This paper describes the use of a microfocused high power pulsed Nd:YAG laser to ablate the corrosion layer in a series of controlled steps while monitoring the composition of the exposed surface using focused proton-induced X-ray emission (PIXE) and RBS in the external beam facility of the Oxford scanning proton microprobe (SPM). The region of the surface removed by the laser is typically less than 500 mum in diameter and so by comparison with other sampling techniques, the effect on the appearance of an object is minimal. Analysis of a spot this size requires a focused proton beam. The modification to the facility to allow the precise registration of the laser beam and the ion beam are described and preliminary results on corroded bronzes are presented. (C) 2001 Elsevier Science B.V. All rights reserved.